Genetic predisposition of six well‐defined polymorphisms in HMGB1/RAGE pathway to breast cancer in a large Han Chinese population. Issue 10 (31st May 2016) - Yue, Liling; Zhang, Qibing; He, Lan; Zhang, Minglong; Dong, Jing; Zhao, Dalong; Ma, Hongxing; Pan, Hongming; Zheng, Lihong
Abstract: Breast cancer constitutes an enormous burden in China. A strong familial clustering of breast cancer suggests a genetic component in its carcinogenesis. To examine the genetic predisposition of high mobility group box‐1/receptor for advanced glycation end products (HMGB1/RAGE) pathway to breast cancer, we genotyped six well‐defined polymorphisms in this pathway among 524 breast cancer patients and 518 cancer‐free controls from Heilongjiang province, China. There were no deviations from Hardy–Weinberg equilibrium for all polymorphisms. In single‐locus analysis, the frequency of rs1800624 polymorphism mutant A allele in RAGE gene was significantly higher in patients than in controls (24.52% versus 19.50%, P = 0.006), with the carriers of rs1800624‐A allele being 1.51 times more likely to develop breast cancer relative to those with rs1800624‐GG genotype after adjustment (95% confidence interval or CI: 1.17–1.94, P = 0.001). In HMGB1 gene, haplotype analysis did not reveal any significance, while in RAGE gene, haplotypes C‐T‐A and C‐A‐G (alleles in order of rs1800625, rs18006024, rs2070600) were significantly associated with an increased risk of breast cancer (adjusted OR = 2.72 and 10.35; 95% CI: 1.20–6.18 and 1.58–67.80; P = 0.017 and 0.015 respectively). In further genetic score analysis, per unit and quartile increments of unfavourable alleles were significantly associated with an increased risk of breast cancer after adjustment (odds ratio or OR = 1.20 and 1.26; 95% CI: 1.09–1.32 and 1.12–1.42; P < 0.001 and <0.001 respectively). Our findings altogether demonstrate a significant association between RAGE gene rs1800624 polymorphism and breast cancer risk, and more importantly a cumulative impact of multiple risk associated polymorphisms in HMGB1/RAGE pathway on breast carcinogenesis.